Effects of ballistic training on preseason preparation of elite volleyball players - Newton, R. U.; Kraemer, W. J.; Häkkinen, K. (Medicine & Science in Sports & Exercise, 1999)
The results of this study lend support to the effectiveness of ballistic resistance training for improving vertical jump performance in elite jump athletes.